Asymptomatic hepatitis B carriers who were vaccinated at birth. Issue 8 (28th March 2019) - Wang, Xueyan; Chen, Qinyan; Li, Hai; Wang, Chao; Hu, Liping; Yang, Qingli; Ren, Chuangchuang; Liu, Huabing; Zheng, Zhigang; Harrison, Tim J.; Fang, Zhong‐Liao
Abstract: The long‐term persistence of immunity following universal infant immunization against hepatitis B virus (HBV) and the need for a subsequent booster dose in adolescence remain under debate. With data derived from Long'an County, Guangxi, China, we reported previously that the prevalence of hepatitis B surface antigen (HBsAg) among adults born from 1987 to 1993 increases with age, although these individuals had received a first dose of the vaccine within 24 hours of birth. Here, we sought the source of transmission by comparison of genotypes among their family members using phylogenetic analysis of complete HBV S gene sequences. For comparison, we screened 2199 vaccinated individuals aged 5 to 17 in Cang Wu County and 1592 vaccinated individuals aged 3 to 7 in Ling Shan County in Guangxi for HBsAg carriers and investigate their family members. In total, 50 asymptomatic HBsAg carriers who were vaccinated at birth and 152 family members were analyzed. The results showed that 25% (95% CI: 6.0‐44.0) of the HBsAg‐positive children had not acquired their HBV infection from their mothers. This phenomenon showed a trend that increases with age. Antibody escape mutations were detected in 22.9% (95% CI: 11.0‐34.8) of the isolates. In conclusion, a booster dose may be necessary for adolescence who were vaccinated at birth in highly endemic countries.